Optimasi Suhu Reaksi Transesterifikasi Pada Minyak Jerami Padi (Oryza sativa L.) Menjadi Biodiesel Dengan Menggunakan Katalis CaO Dari Kulit Telur Ayam) - Tasik Sinta; Daniel Tarigan; Chairul Saleh (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2016)
The research on optimization of transesterification temperature for production of biodiesel from rice straw oil (Oryza sativa L.) using CaO catalyst derived from the chicken egg skin has been conducted. Production of biodiesel was conducted at varied temperatures, namely 30oC, 40oC, 50oC, 60oC and 70oC. The fatty acid compositions of the transesterification products were determined by using GC-MS and the physical and chemical characteristics were determined using SNI Methods 04-7182-2006. The AAS result suggested that the chicken egg skin contained 91.41% CaO. The optimum transesterification temperature was 60oC producing 90,8405% methyl ester. The results of GC-MS showed that the highest percentage of fatty acid was methyl oleic (44.56%).